Rhabditid nematodes found from a rocky coast contaminated with treated wastewater of Casey Station in East Antarctica, with a description of a new species of Dolichorhabditis Andrassy, 1983 (Nematoda: Rhabditidae) - Kito, Kenji; Ohyama, Yoshikuni (Zootaxa, 2008)
Three unknown species of rhabditid nematodes were found from sediment collected in a rocky coast area at Budd Coast, Wilkes Land, East Antarctica. The sediment was contaminated with treated wastewater which had been discharged through a pipeline extending from Casey Station (Australia). The most abundant of the three species is described here as Dolichorhabditis tereticorpus sp. n. based on female specimens. Dolichorhabditis tereticorpus resembles Dolichorhabditis dolichuroides (Anderson & Sudhaus, 1985) but is distinguished by the features of body length, pharyngeal corpus, and vulval lips. The remaining two undetermined species, Rhabditidae sp. 1 and Rhabditidae sp. 2, are briefly reported because the specimens obtained were inadequate in condition or number for detailed taxonomic analysis. It is suggested that these three species are peculiar to this rocky coast, although it is not certain yet whether they are specific to the habitat contaminated with the discharged effluent of the station.